2014
DOI: 10.1182/blood-2014-04-571679
|View full text |Cite
|
Sign up to set email alerts
|

P2X1 expressed on polymorphonuclear neutrophils and platelets is required for thrombosis in mice

Abstract: Key Points• Activation of PMNs at the site of injury is required for thrombin generation.• P2X1 receptor expressed on both PMNs and platelets is crucial to initiate thrombosis.Adenosine triphosphate (ATP) and its metabolite, adenosine, are key regulators of polymorphonuclear neutrophil (PMN) functions. PMNs have recently been implicated in the initiation of thrombosis. We investigated the role of ATP and adenosine in PMN activation and recruitment at the site of endothelial injury. Following binding to the inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 40 publications
3
75
0
Order By: Relevance
“…Thus, modulation of P2X1 has mainly indirect effects by activation of circulating, but not parenchymal, cells. This finding is supported by recent studies that have shown the relevance of P2X1 in other models of inflammation and injury, such as neutrophil migration during endotoxemia . Desensitization is an inherent property of P2X1 receptor and explains decreased secretion of IL‐22 ex vivo and in vivo in the absence of CD39 on liver lymphocytes .…”
Section: Discussionsupporting
confidence: 74%
“…Thus, modulation of P2X1 has mainly indirect effects by activation of circulating, but not parenchymal, cells. This finding is supported by recent studies that have shown the relevance of P2X1 in other models of inflammation and injury, such as neutrophil migration during endotoxemia . Desensitization is an inherent property of P2X1 receptor and explains decreased secretion of IL‐22 ex vivo and in vivo in the absence of CD39 on liver lymphocytes .…”
Section: Discussionsupporting
confidence: 74%
“…The exteriorization of cremaster muscle for 5 h may potentially induce inflammation. However, similar to models described by others343536, the cremaster muscle is superfused with thermocontrolled bicarbonate-buffer solution, which efficiently suppresses the development of a spontaneous inflammatory response. Indeed, while validating this model, no inflammation was observed when the cremaster muscle was exposed to a control gel (agarose/PBS) during at least 5 h. Therefore, the inflammatory response observed is selectively due to the presence of TNFα in the gel.…”
Section: Discussionmentioning
confidence: 99%
“…This has been highlighted in a specific model of neutrophil-dependent thrombosis of cremasteric arterioles triggered by laser injury, where activation of the neutrophil by guest on May 9, 2018 http://atvb.ahajournals.org/ Downloaded from P2X 1 receptor appeared to be indispensable for neutrophil recruitment and subsequent fibrin generation and thrombus formation at the site of vessel injury. 58 Whether this role of the P2X 1 receptor may be relevant under other conditions of vascular inflammation is an open question. Overall, this receptor nonetheless plays an important role in thrombosis and inflammatory processes, indicating that it could constitute an interesting target for new therapeutics in these fields.…”
Section: P2x 1 Receptor In Inflammationmentioning
confidence: 99%